Um reator piezoelétrico acoplado a um analisador em fluxo-batelada para extração sonoquímica e determinação de catalase e lipase em fígados bovinos e avícola com detecção por filmagem digital - Siqueira, Lucas Alfredo (2020)
The catalase enzyme is part of a group of substances with antioxidant function and that prevent attacks of free radicals to cellular and intracellular membranes. Lipase is another enzyme, which is responsible for regulating the levels of triacylglycerol in the bloodstream. The nutritional deficiency of these enzymes can result in several types of diseases such as: cancer, diabetes, atherosclerosis, neurodegenerative diseases and Alzheimer's. The animal liver is an important food source of the aforementioned enzymes and to evaluate the enzyme levels of catalase and lipase present in samples of this food, an enzyme extractor was developed in this project, based on a sonochemical process, coupled to a batch flow analyzer, using as a detection system a webcam FBA-PR (digital filming). The proposed enzymatic extractor was used as a pretreatment step for the samples in the extraction of the studied enzymes, and its main components are a microcontroller and a piezoelectric reactor. Taguchi planning was used to choose the best extraction conditions. Catalase was determined by monitoring the decomposition of H2O2 into O2 and H2O using the webcam. For the lipase the chemical reaction between the triacylglycerol and the lipase was monitored, releasing fatty acids that are quantified by automatic titration. The FBA-PR by digital filming was applied to determine the activity of catalase and lipase in liver, bovine and poultry samples. For catalase the results showed relative errors between -1.98 and 1.96% and relative standard deviation less than 2%, in bovine liver samples and relative errors between -2.03 and 2.08% and with standard deviation relative less than 3% for poultry liver samples. The results for lipase in bovine liver obtained a relative error between -0.65 and 0.76% and a relative standard deviation of less than 2%, and for poultry liver samples, the relative error varied between -0.55 and 0, 64%, with a relative standard deviation of less than 2%. The paired t-test was applied at a statistical confidence level of 95% and no significant differences were observed for both enzymes. The FBA-PR by digital filming obtained an analytical frequency of 72 h-1 for catalase and 69 h-1 for lipase, with a total spent volume of samples and reagents of 1.2 mL and 1.6 mL, respectively. Thus, the FBA-PR (digital filming) proves to be suitable for the extraction of enzymes, with a lower consumption of reagents and samples, and by enabling the achievement of sensitive, reproducible and reliable results.